Modal Sosial: Seberapa Penting di dalam Keberhasilan Pemberdayaan Nelayan - Jumiati Jumiati; Hidayatul Fajri (Jurnal Teori dan Riset Administrasi Publik, 2018)
Empowerment is a process of strengthening and developing personal and community capacity. Thus, the success or failure of empowerment depends on how much the community is able to capitalize on the capital and develop the capacity they have. The main argument in this study is the difference in empowerment success caused by the role of social capital in the community. This research is in the form of a case study conducted in Painan Selatan Village and Carocok Anau Village. Using a semi-structured approach by conducting in-depth interviews. The results showed that fishermen in Painan Selatan Village were able to strengthen trust, increase participation and develop their social values, conditions that were not found in the Carocok Anau Village. This is due to differences in their perceptions of empowerment. Painan Selatan fishermen formulate empowerment as an ongoing process while Carocok Anau Village fishermen consider empowerment as a program sourced from the government.